2015
DOI: 10.1158/1541-7786.mcr-14-0492
|View full text |Cite
|
Sign up to set email alerts
|

Variants of Osteoprotegerin Lacking TRAIL Binding for Therapeutic Bone Remodeling in Osteolytic Malignancies

Abstract: Osteolytic bone damage is a major cause of morbidity in several metastatic pathologies. Current therapies using bisphosphonates provide modest improvement, but cytotoxic side effects still occur prompting the need to develop more effective therapies to target aggressive osteoclastogenesis. Increased levels of Receptor Activator of Nuclear Factor Kappa B Ligand (TNFSF11/RANKL), leading to RANKL-RANK signaling, remains the key axis for osteoclast activation and bone resorption. Osteoprotegerin (TNFRSF11B/OPG), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 48 publications
2
10
0
Order By: Relevance
“…The functionality of mutant OPG proteins in terms of inhibiting osteoclastogenesis was determined, as previously described. 24 Briefly, RAW 264.7 cells were cultured in 24well plates (1 × 10 4 cells/well) for 10 days in the presence of 100 ng/mL recombinant RANKL (a kind gift from Dr Xu Feng, UAB), either alone or in combination with conditioned medium from plasmid transfected cells with either OPG WT or OPG Y49R . The medium was changed every 48 hours for 10 days, following which tartrate-resistant acid phosphatase (TRAP) staining was performed using Leukocyte Acid Phosphatase kit (MilliporeSigma), as per manufacturer's instruction to enumerate multinucleated TRAP-positive osteoclasts.…”
Section: Osteoclast Differentiation Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The functionality of mutant OPG proteins in terms of inhibiting osteoclastogenesis was determined, as previously described. 24 Briefly, RAW 264.7 cells were cultured in 24well plates (1 × 10 4 cells/well) for 10 days in the presence of 100 ng/mL recombinant RANKL (a kind gift from Dr Xu Feng, UAB), either alone or in combination with conditioned medium from plasmid transfected cells with either OPG WT or OPG Y49R . The medium was changed every 48 hours for 10 days, following which tartrate-resistant acid phosphatase (TRAP) staining was performed using Leukocyte Acid Phosphatase kit (MilliporeSigma), as per manufacturer's instruction to enumerate multinucleated TRAP-positive osteoclasts.…”
Section: Osteoclast Differentiation Assaymentioning
confidence: 99%
“…14 Similar to clinical reports with molecular alteration in TNFRSFassociated pathologies, we previously identified that mutations on key TRAIL-binding residues in OPG result in similar delay in subcellular protein trafficking. 24 In our quest to mitigate the limitations of a clinical use of OPG in skeletal remodeling for osteolytic malignancies, we endeavored uncoupling the bispecific function of OPG from sequestering tumor-necrosis factor-related apoptosis-inducing ligand (TRAIL). During this process, we have identified key domains involved in TRAIL binding and generated OPG variants lacking the structural determinant for TRAIL binding.…”
Section: Introductionmentioning
confidence: 99%
“…17 The recombinant OPG used comprises the ligand-binding domain of human OPG (1-201 amino acids), fused to the Fc domain of human immunoglobulin G in pcDNA3.1 vector, under the control of cytomegalovirus promoter. Variants of OPG containing mutations Y49R and F107A were created by sitedirected mutagenesis as described earlier.…”
Section: Production Of Recombinant Adeno-associated Virus Expressing Opgmentioning
confidence: 99%
“…Variants of OPG containing mutations Y49R and F107A were created by sitedirected mutagenesis as described earlier. 17 To generate recombinant adeno-associated virus (rAAV) plasmids containing wild-type (WT) or mutant OPG, the open reading frame, encoding the transgene was excised from pcDNA3.1 and subcloned into the multicloning site (MCS) of rAAV plasmid. Packaging and production of rAAV-OPG WT/mut were performed by transient transfection in 293 cells with the helper plasmid pDP6 using an established protocol as described earlier.…”
Section: Production Of Recombinant Adeno-associated Virus Expressing Opgmentioning
confidence: 99%
See 1 more Smart Citation